Active simulation of electronically tunable grounded lossless inductor using voltage differencing inverting buffered amplifiers - Roongmuanpha, Natchanai; Unhavanich, Sumalee; Tangsrirat, Worapong (My University, 2018)
An actively simulated grounded lossless inductor based on employing voltage differencing inverting buffered amplifiers (VDIBAs) as new active components has been presented. The synthetic canonical inductor uses only two VDIBAs and one grounded capacitor. The simulator provides the advantage feature of electronic control of its equivalent inductance via the transconductance parameter of the VDIBA, and also does not need critical element matching conditions. An illustrative application of the proposed tunable grounded lossless inductor on the realization of an active RLC second-order bandpass filter has been designed. The usability of the proposed circuit has been evaluated using PSPICE simulations based on VDIBA implemented in TSMC 0.25-μ m CMOS technology, and the simulated results demonstrate a sufficient agreement with the theoretical conclusions.
Keywords: electronically tunable circuit; inductance simulator; lossless inductor; Voltage Differencing Inverting Buffered Amplifier (VDIBA)